Bahasa Inggeris - Ramadhani, Ressita; Rafee, Abidah (Centre For Tourism Planning and Development, 2024)
The global tourism industry has suffered significant losses due to the impact of global pandemic Covid-19. This paper examines the policies and efforts adopted by the local authorities of Indonesia and Brunei Darussalam to support their sustainable tourism industries and it seeks to draw lessons from both countries. The research will primarily focus on ecotourism issues and challenges in specific areas such as national parks, natural landscapes, and historical sites in both countries. Specific destinations within these eco-tourism categories for Indonesia’s; Bogor Botanical Garden, Onrust Archeological Park in Thousand Island Jakarta, and North Sulawesi Mountain Landscape. For Brunei Darussalam’s; Kampong Ayer, Sumbiling Eco-Village, and Ulu Temburong National Park. This study reveals challenges in tourism industry stakeholders’ participation level, inadequate and improper tourism infrastructure, a lack of skilled workforce employment. and insufficient public education on eco-tourism in both nations. Recommendations emphasize the importance of capacity building for stakeholder collaboration, infrastructure acquisition, and technology-driven knowledge transfer. The limitations of this study lie in the scarcity of research on empirical study and the unavailability of high-level official interviews. Therefore, for future research, it is important to assess the effectiveness of Indonesia and Brunei Darussalam government’s direct response such as funding mechanism policy, infrastructures development policy, and the utilization of digital platform policy. Besides, it is also important to assess the Indonesia and Brunei Darussalam government’s response to and anticipation of ecotourism issues for both countries.